A Study on Secure Sharing of Application Data in Cloud Computing - Naik, P. Kiran Kumar; Babu, GV. Ramesh (International Journal of Computer Sciences and Engineering, 2025)
Cloud clients utilizes "Cloud storage" administration to have their information in the cloud. Get to control benefit gave by cloud is accustomed to giving assurance against unapproved access to information. Cipher text-Policy Attribute-Based Encryption (CP-ABE) is generally considered for information get to control in distributed storage. The current CP-ABE is hard to apply in multi-specialist distributed storage because of the characteristic repudiation issue. The proposed revocable multispecialist CP-ABE plot gives answer for the characteristic denial issue. The proposed plot refreshes the segments of the disavowed quality just and produces most recent mystery keys for the repudiated credit and advances it to the non renounced clients who have the properties as denied traits. The Backward security and Forward security is kept up. On the off chance that the repudiated client goes into the framework again by doing the enlistment procedure implies, the specific client is recognized by means of the character card detail in the renouncement rundown and they are not permit in the framework, so that these clients are halted at the enrolment stage itself.